2020
DOI: 10.4143/crt.2019.457
|View full text |Cite
|
Sign up to set email alerts
|

EBV-miR-BHRF1-1 Targets p53 Gene: Potential Role in Epstein-Barr Virus Associated Chronic Lymphocytic Leukemia

Abstract: PurposeThe purpose of this study was to investigate the prognostic impact of Epstein-Barr virus (EBV)–microRNA (miRNA, miR)-BHRF1-1 with chronic lymphocytic leukemia (CLL) as well as role of EBV-miR-BHRF1-1 in p53 gene.Materials and MethodsQuantitative reverse transcription–polymerase chain reaction and western blotting were used to quantify EBV-miR-BHRF1-1 and p53 expression in cultured CLL.Resultsp53 aberration was associated with the higher expression level of EBV-miR-BHRF1-1 (p < 0.001) which was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…We discovered that the levels of EBV miRNA BHRF1-1 expression in the B-cells of CLL cases were substantially greater than in healthy ones. The expression of BHRF1-1 in CLL cases ranged from 0.31 -9.0 with a median (IQR) of 3.63 (2.12 -4.44) and in control group from 0.02 -1.30 with a median (IQR) of 0.31 (0.13 -0.81), that in line with similar findings demonstrated by Visco et al [25] and Xu et al [26] who found CLL patients had greater EBV-BHRF1-1 levels than the healthy control group. This finding is consistent with earlier research and is owing to its essential involvement in B-cell differentiation and the prevention of apoptotic processes.…”
Section: Discussionsupporting
confidence: 90%
“…We discovered that the levels of EBV miRNA BHRF1-1 expression in the B-cells of CLL cases were substantially greater than in healthy ones. The expression of BHRF1-1 in CLL cases ranged from 0.31 -9.0 with a median (IQR) of 3.63 (2.12 -4.44) and in control group from 0.02 -1.30 with a median (IQR) of 0.31 (0.13 -0.81), that in line with similar findings demonstrated by Visco et al [25] and Xu et al [26] who found CLL patients had greater EBV-BHRF1-1 levels than the healthy control group. This finding is consistent with earlier research and is owing to its essential involvement in B-cell differentiation and the prevention of apoptotic processes.…”
Section: Discussionsupporting
confidence: 90%
“…Tumor protein p53, or simply p53, is closely related to the occurrence of gastric cancer, and many studies find EBV infection to be associated with p53 methylation (21)(22)(23). In 2019, Camargo et al found that EBV-positive gastric cancer cases lack the TP53 mutation, suggesting that serological characteristics may provide information for viral carcinogenesis.…”
Section: Detection Of Anti-ebv and Anti-p53 Antibodiesmentioning
confidence: 99%
“…Several predicted targets of EBV-encoded miR-NAs were detected by computational prediction, and some of these were functionally investigated using an in vitro assay [36]. BHRF1 miRNAs, which encode three pri-miRNAs, show almost undetectable expression in EBV (+) GC; thus, their functional roles in lytic infection, in regulating host cell cycle and viral infection, and in progeny production, were revealed in various types of malignancy rather than in GC [37][38][39][40][41][42][43][44][45]. In GC specifically, BART miRNAs encoding 44 mature miRNAs may disrupt genes involved in apoptosis and cell cycle regulation, as confirmed in EBV (+) GC (Table 1) [2,10,36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Ebv-encoded Mirnasmentioning
confidence: 99%